2023
DOI: 10.21037/jtd-23-230
|View full text |Cite
|
Sign up to set email alerts
|

Measuring cough: what really matters?

Abstract: The clinical and research discipline of cough has grown substantially over the last two decades as methods to measure cough have developed and evolved. Cough can be thought of both as a symptom and an objectively observable pathophysiological phenomenon, two aspects whose interrelationship is complicated. The following review explores the varied methods to measuring cough, both subjective, patient-reported measures and objective approaches. Specifically, symptom scores, questionnaires of cough-related quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
(86 reference statements)
0
5
0
Order By: Relevance
“… 36 There was only moderate correlation between cough severity VAS score and LCQ score. 37 What is more, the perception of the impact on quality-of-life has individual variances due to age, education, social background, and so on.…”
Section: Discussionmentioning
confidence: 99%
“… 36 There was only moderate correlation between cough severity VAS score and LCQ score. 37 What is more, the perception of the impact on quality-of-life has individual variances due to age, education, social background, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…12 There are several limitations of this analysis. The exploratory post hoc nature limits interpretation; the assessment of antitussive use was limited to reports of concomitant medication (because it was not a prespecified outcome of EXTRA); and an objective, subjective, or patient-reported measure of cough (such as those considered by Turner et al 13 ) was not assessed. In addition, though expected to be uncommon in a clinical trial, there is a possibility of non-reported selfmedication of antitussives.…”
Section: Discussionmentioning
confidence: 99%
“…One problem for studies in this area was poor recording and classification in healthcare databases due to a lack of specific coding for chronic cough. This changed in 2022, as the World Health Organization International Classification of Diseases (10 th revision) introduced a code for chronic cough (R05.3), hopefully enabling chronic cough to be increasingly recognised and recorded as a discrete disease in its own right, rather than a symptom of another disorder [ 29 ].…”
Section: Looking Ahead: Further Unmet Needsmentioning
confidence: 99%
“…Despite multiple objective and subjective options for measuring cough, diagnoses of chronic cough can be difficult. Tools to measure objective cough frequency, cough severity and cough-specific quality of life are used in clinical and research settings, and have been essential for progress [ 2 , 22 , 29 ]. However, there is currently no gold standard investigation for a diagnosis of (refractory or unexplained) chronic cough, and a limited availability of cough frequency monitoring or tussive challenge testing for general use.…”
Section: Looking Ahead: Further Unmet Needsmentioning
confidence: 99%
See 1 more Smart Citation